Antigen dose and humoral immune response correspond with protection for inactivated infectious pancreatic necrosis virus vaccines in Atlantic salmon (Salmo salar L) - Munang'andu, Hetron Mweemba; Fredriksen, Børge Nilsen; Mutoloki, Stephen; Dalmo, Roy Ambli; Evensen, Øystein (Veterinary Research, 2013)
An enduring challenge in the vaccinology of infectious pancreatic necrosis virus (IPNV) is the lack of correlation between neutralizing antibodies and protection against mortality. To better understand the immunological basis of vaccine protection, an efficacy trial including Atlantic salmon (Salmo salar L.) vaccinated with a high antigen (HiAg) or low antigen (LoAg) dose vaccine was carried out in a cohabitation challenge model using the highly virulent Norwegian Sp strain NVI015. To pinpoint the immunological basis of vaccine protection, pathogenic mechanisms of IPNV were unraveled in control fish while obtaining feedback on mechanisms of protection in the vaccinated fish. During the incubation period, infection rates were highest in control fish, followed by the LoAg group with the lowest infections being in the HiAg group. Although both the liver and pancreas are target organs prone to tissue damage, infection in the liver was delayed until acute infection in most fish. A correlate of pathology determined as the cutoff threshold of viral copy numbers linked to tissue damage in target organs was estimated at ≥ 107.0, which corresponded with an increase in mortality. The kinetics of IFNα and Mx expression suggests that these genes can be used as biomarkers of IPNV infection progression. Mechanisms of vaccine protection involved reducing infection rates, preventing infection of the liver and reducing virus replication in target organs to levels below the correlate of pathology. Overall, the study shows that antigen dose corresponds with vaccine efficacy and that antibody levels can be used as a signature of protective immunity against pathological disease and mortality.